DNA barcoding of kelampayan (Neolamarkia cadamba) progenies (half sib family) using ISSR markers - Moh, Ivy Heng Shi (Universiti Malaysia Sarawak, (UNIMAS), 2011)
Neolamarckia cadamba (Kelampayan) is a multipurpose and fast growing plantation tree species. Nowadays, the research done on the Kelampayan trees is very limited. In this study, DNA barcoding of Kelampayan was carried out using the inter simple sequence repeat (ISSR) markers. The DNA was extracted from the plant leaves using fasTip-X method. Three ISSR primers which are (ACC)6G, (AC)8G and (AC)8T were used to determine the genetic relatedness of the Kelampayan progenies (half-sib family). A total of 94 loci were generated in order to determine the genetic relatedness for the progenies. Data analysis was carried out using NTSYS-pc and dendrogram was constructed using UPGMA method. The unrooted neighbour-joining tree was constructed also in order to get a more accurate result. From the dendograms and unrooted neighbourjoining trees constructed, the mother trees and progenies were been grouped into two clusters, cluster I and cluster II. The average similarity based on Jaccard’s similarity coefficient calculated was in the range of 0.433 to 0.584. This indicate that there are no self pollination occur for the Kelampayan. The ISSR markers were successfully been used to determine the genetic relatedness of Kelampayan mother trees and progenies.